Revisiting shyness and sociability: a preliminary investigation of hormone-brain-behavior relations - Tang, Alva; Beaton, Elliott A.; Schulkin, Jay; Hall, Geoffrey B.; Schmidt, LouisA. (Frontiers in Psychology, 2014)
Shyness and sociability are two fundamental personality dimensions that are conceptually and empirically orthogonal and are conserved across cultures, development, and phylogeny. However, we know relatively little regarding how shyness and sociability are represented and maintained in the brain. Here we examined neural responses to the processing of different types of social threat using event-related fMRI, the salivary cortisol awakening response (CAR), and sociability in young adults selected for high and low shyness. Shy adults who exhibited a relatively higher CAR displayed neural activity in putative brain regions involved in emotional conflict and awareness, and were more sociable. In contrast, shy adults who displayed a relatively lower CAR exhibited neural activity in putative brain regions linked to fear and withdrawal, and were unsociable. Results revealed no systematic brain responses to social threat processing that correlated with the CAR in nonshy adults. These preliminary results suggest that individual differences in waking morning cortisol levels may influence neural processes that facilitate either social approach or withdrawal among people who are shy. Findings are discussed in relation to their theoretical and clinical implications for moving beyond longstanding descriptive to explanatory models of shyness and sociability and for understanding individual differences in social behavior in general.